2002
DOI: 10.1161/hy02t2.102809
|View full text |Cite
|
Sign up to set email alerts
|

Substance P in Subtotal Nephrectomy-Salt Hypertension

Abstract: Abstract-We have previously demonstrated that calcitonin gene-related peptide (CGRP) plays a counterregulatory role in subtotal nephrectomy-salt (SN-salt) hypertension through an increase in vascular responsiveness to the dilator activity of this neuropeptide. Substance P (SP) is often co-localized with CGRP in perivascular sensory nerves. To determine the role and mechanism of action of SP in SN-salt hypertension, we induced hypertension in 4-to 6-week-old male Sprague-Dawley rats (nϭ8) by subtotal nephrectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Our studies also suggested that the depressor effect of SP is mediated, at least in part, through the interaction of SP with vascular NK-1 receptors. Quantification of DRG SP mRNA and peptide levels revealed no significant increase in SP mRNA or protein in the SN-salt rats (N = 8) compared to two groups (N = 8/group) of controls (sham operated with either tap water or saline drinking water) (43). This is similar to what was found for CGRP expression in this setting.…”
Section: Role Of Substance P In Subtotal Nephrectomy-salt and Deoxycosupporting
confidence: 83%
See 1 more Smart Citation
“…Our studies also suggested that the depressor effect of SP is mediated, at least in part, through the interaction of SP with vascular NK-1 receptors. Quantification of DRG SP mRNA and peptide levels revealed no significant increase in SP mRNA or protein in the SN-salt rats (N = 8) compared to two groups (N = 8/group) of controls (sham operated with either tap water or saline drinking water) (43). This is similar to what was found for CGRP expression in this setting.…”
Section: Role Of Substance P In Subtotal Nephrectomy-salt and Deoxycosupporting
confidence: 83%
“…In DOC-salt rats iv Span-II caused a rapid increase in MAP compared to controls (9.3 ± 1.5 vs 0.9 ± 2.2 mmHg) (42). In SN-salt rats, iv Span-II also significantly elevated MAP (13.9 ± 0.8 vs 1.7 ± 1.7 mmHg) (43). Our studies also suggested that the depressor effect of SP is mediated, at least in part, through the interaction of SP with vascular NK-1 receptors.…”
Section: Role Of Substance P In Subtotal Nephrectomy-salt and Deoxycosupporting
confidence: 66%
“…Therefore, the lack of a subsequent decrease in blood pressure despite the use of benidipine paradoxically indicated that the drug could not exert an antihypertensive effect at this advanced stage of CRF. According to previous studies, the pathophysiological mechanisms that contribute to the maintenance of severe hypertension in end-stage renal disease include sodium and volume overload, inappropriate renin secretion, sympathetic nervous system activity, electrolyte disturbances, and alterations in endothelin and nitric oxide [27,28,29]. In the present study, the administration of 5 mg/kg benidipine alone was unlikely to be sufficient to overcome these mechanisms and decrease the severely elevated blood pressure in rat models with advanced CRF.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic studies were then performed ϳ3 h after surgery with the animals in a fully awake and unrestrained state. Our laboratory (29,50) has previously validated the use of the CGRP and NK1 receptor antagonists by showing that CGRP8-37 (50 and 200 g) and spantide II (350 g) could completely block the hypotensive effects of exogenously administered CGRP and SP, respectively. These same doses were used in the current study.…”
Section: Methodsmentioning
confidence: 99%